STRATEGIES FOR PREVENTING VOTE BUYING AND ENFORCING VILLAGE APPARATUS NEUTRALITY IN THE 2024 ELECTIONS - Annisa Gusniar; Tabah Maryanah; Robi Cahyadi Kurniawan (Journal of Social Politics and Governance (JSPG), 2026)
This study aims to analyze strategies for preventing vote buying and enforcing the neutrality of village officials in the 2024 General Election in East Lampung Regency within the context of the open list proportional electoral system. The study focuses on the persistence of vote buying practices and indications of non-neutral behavior among village officials that potentially undermine electoral integrity at the local level. This research applies Arend Lijphart’s (1994) electoral system theory, which argues that electoral system design influences political competition and the behavior of electoral actors. A descriptive qualitative approach was employed, with data collected through in-depth interviews and documentation techniques involving election organizers, election supervisory bodies, and village officials. The findings indicate that the open list proportional system intensifies personalized competition among candidates, including within the same political party, thereby encouraging transactional practices such as vote buying to secure electoral support. The study also identified indications of violations of village officials’ neutrality, although many cases were not formally reported. Therefore, strengthening political education for voters, neutrality training for village officials, participatory monitoring mechanisms, and accessible public reporting systems is necessary to improve electoral integrity and transparency.